2017
DOI: 10.2147/ndt.s127453
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of olanzapine/fluoxetine combination in the treatment of treatment-resistant depression: a meta-analysis of randomized controlled trials

Abstract: BackgroundWhether olanzapine/fluoxetine combination (OFC) is superior to olanzapine or fluoxetine monotherapy in patients with treatment-resistant depression (TRD) remains controversial. Thus, we conducted this meta-analysis of randomized controlled trials (RCTs) to compare the efficacy and safety of OFC with olanzapine or fluoxetine monotherapy for patients with TRD.Materials and methodsRCTs published in PubMed, Embase, Web of Science, and the ClinicalTrials.gov registry were systematically reviewed to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
0
18
1
1
Order By: Relevance
“…The MPG recommended OFC as a first-line option, stating that it is well researched and generally well tolerated, and suggested that olanzapine augmentation of a TCA may also be effective, as may olanzapine monotherapy ( Takahashi et al, 2008 ). The MPG highlighted the risk of weight gain and limited clinical experience outside the United States and the fact that most available data are related to bipolar disorder ( Luan et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The MPG recommended OFC as a first-line option, stating that it is well researched and generally well tolerated, and suggested that olanzapine augmentation of a TCA may also be effective, as may olanzapine monotherapy ( Takahashi et al, 2008 ). The MPG highlighted the risk of weight gain and limited clinical experience outside the United States and the fact that most available data are related to bipolar disorder ( Luan et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Where the illness has not responded sufficiently to antidepressant medication, a further pharmacological strategy that is recommended in treatment guidelines for depression is the addition of an antipsychotic medication. 1,3,12 There is most evidence to support the use of quetiapine, 21 olanzapine, 22 aripiprazole, 23 or risperidone. 24 We found that augmentation with one of these four antipsychotic medications was the most common pharmacological strategy employed in routine clinical practice in mental health services, being used in a third of those with moderate depression and two-thirds of those with severe depression.…”
Section: Discussionmentioning
confidence: 99%
“…As there is strong evidence for the efficacy of combination or augmentation psychotropic therapy for treatment‐resistant depression, 38,39 polypharmacy of psychotropics is sometimes used for individuals with severe mental conditions. However, inappropriate prescribing of psychotropics has become a worldwide problem 40‐42 .…”
Section: Discussionmentioning
confidence: 99%